The advertisement call of Pristimantis unistrigatus (Anura: Strabomantidae) from the Ecuadorian Andes - Chaves Acuña, Wagner Josue (2023)
Pristimantis unistrigatus regularly calls during day and night in a wide variety of habitats, ranging from mesic undisturbed ecosystems (e.g., Eucalyptus–pasture habitat, paramo) to urbanized valleys and cities. This frog can be typically found either inside bromeliads that are close to the ground (< 3 m height) or hidden underground beneath rocks, logs, and/or construction materials. However, despite its relative abundance, information about the reproductive biology of the species remains scarce. To date, information about the life history and bioacoustics of the species remains scarce as there is no formal characterization of the advertisement call of P. unistrigatus. Here we provide a quantitative and qualitative characterization of its advertisement call, accounting for temporal, spectral, and structural parameters.